"Challenge Me!": Using Confirmation Theory to Understand Coach Confirmation as an Effective Coaching Behavior. (April 2018) - Cranmer, Gregory A.; Brann, Maria; Weber, Keith D.
Confirmation theory is a theoretical framework that forwards that the communication of acceptance and challenge to recipients promotes prosocial environments that foster positive affect, attitudes, and behaviors. This study utilized confirmation theory to better understand the influence of coaches' use of confirmation on athletes' satisfaction and motivation to play their sport. Data collected from 132 former high school athletes indicated that the challenge dimension of coach confirmation uniquely and strongly predicts athletes' satisfaction with their sport experiences, satisfaction with their communication with head coaches, and their motivation to play. These findings emphasize sport as a unique context of confirmation in which athletes prioritize their development and constructive criticism and demonstrate that confirmation is an effective coaching behavior that should be integrated into coaches' everyday practices.